Classification Fertility Preference among Married Woman in East Java, Indonesia Using Naive Bayes Classification - Rhea Rahma Adelina; Diah Indriani; Kuntoro (Indian Journal of Forensic Medicine & Toxicology, 2021)
Fertility preference have an important role in achieving birth rates. According to the most recent IndonesianDemography and Health Survey, 2017, total fertility rate in east java has reached target of 2.1 children butthe desired birth rate has increased from 2.0 to 2.1 children. This study examines classification of fertilitypreference in east java, Indonesia using Naïve Bayes. Data come from Indonesia Demography and HealthSurvey (IDHS) 2017, which limited on 2569 married woman in east java. The findings show married womanthat have opportunity to having child again which have secondary complete education, work but have beenout for less than 7 days, have middle wealth index, stay in rural, have age between 25 – 34 old, have moreboys than girl and not using contraception.